Design and construction of a synthetic E. coli protease inhibitor detecting biomachine - P. Boonyalekha (2018)
© 2017 IEEE. Protease inhibitors (PIs) have been used to treat various types of symptoms or diseases. However, current PIs block the protease activity by targeting the protease active site which has been shown to be sensitive to the off-target effect due to crossreactivity with protease homologues. An alternative approach to inhibiting protease activity is to target the substrate, specifically by blocking the substrate cleavage site. We propose to employ synthetic biology approach to create a synthetic E. coli to be used as a protease inhibitor detecting biomachine that can effectively isolate intrabodies, a new generation of protease inhibitor drug. The in vivo selection system, comprised of three biological devices, i.e., protease activity detector, protease generator and protease blocking devices, is based on the ability to transport folded protein of the E. coli twin-arginine translocation (Tat) pathway and antibiotic resistance of TEM-1 β-lactamase (Bla) using as reporter protein. By linking protease degradation to antibiotic resistance, we can isolate the suitable intrabodies simply by plating cells containing appropriate devices on solid agar containing β-lactam ring antibiotics. As a proof of concept, we applied a previously isolated HIV-1 p17 intrabody (scFvp17) that binds to the C-terminus of HIV-1 matrix protein (p17) to our synthetic E. coli. This work demonstrated that binding of scFvp17 to its epitope on p17 can physically interfere with HIV-1 protease activity and inhibit proteolytic cleavage at the p17Δp24 cleavage site when expressed in the designed format. The device was optimized by varying plating conditions such as incubation temperatures, induction levels, and Carbenicillin concentrations which was used as selection pressure. The feasibility of this assay has opened the door to protease inhibitor selection which can be used for various applications such as optimization of the current protease inhibitors and selection of new ones.